Survey of Addiction Specialists’ Use of Medications to Treat Alcohol Use Disorder - Ehrie, Jarrod; Hartwell, Emily E.; Morris, Paige E.; Mark, Tami L.; Kranzler, Henry R. (Frontiers in Psychiatry, 2020)
Objectives: Several medications have been shown to be safe and effective for treating alcohol use disorder (AUD); however, these medications are prescribed infrequently. We conducted a survey of the demographics, practice characteristics, and self-perceived knowledge, experience, and opinions of addiction specialists on the use of AUD medications and how to increase their use. Methods: We sent a 19-question survey to members of the American Society of Addiction Medicine (ASAM) and the American Academy of Addiction Psychiatry (AAAP). Results: We received a total of 395 responses from ASAM members and 194 responses from AAAP members One hundred of the respondents were members of both organizations. The large majority of respondents (92.6%) were prescribers, and 81.6% were non-trainee physicians. The two most frequently used medications for treating AUD were oral naltrexone (27%) and long-acting naltrexone (18%). Respondents were significantly more confident in the strength of the research findings and evidence for the efficacy and safety of naltrexone than other AUD medications (p < 0.001). Respondents identified additional education to current providers about existing medications as the most important potential intervention to increase the use of AUD medications. Conclusions: Compared with a survey published in 2001, in 2018 the proportion of respondents who reported using naltrexone more than doubled and addiction specialists were more confident in their use of AUD medications, rating their efficacy and safety more highly. Consistent with findings from other recent studies, providing more education to practitioners about existing AUD medications may be the most effective way to increase their use.